Molecular detection reveals diverse tick-borne bacterial and protozoan pathogens in two tick species from Yingshan County of Hubei Province, China in 2021–2022 - Zhao, Na; Pan, Kai; Teng, Zhongqiu; Wang, Hongliang; Zhang, Xue; Ren, Hongyu; Yi, Lei; He, Jia; Cai, Kun; Qin, Tian (Frontiers in Microbiology, 2023)
In this study, a total of 179 ticks infesting ruminant livestock, including 166 Haemaphysalis longicornis ticks and 13 Rhipicephalus microplus ticks were collected from Yingshan county of Hubei province, China in 2021-2022. PCR testing and sequence analysis revealed that the ticks infected with various species of pathogens including Rickettsia (R. japonica), Anaplasma (A. bovis, A. ovis, A. platys, and Ca. A. boleense), Ehrlichia (E. minasensis and Ehrlichia sp.), Theileria (T. orientalis and T. luwenshuni), and Babesia (B. bigemina). The infection rates of these pathogens were 0.56%, 16.76%, 7.26%, 2.79% and 0.56%. respectively, while only 3 of 13 R. microplus ticks were detected to be infected wth Ehrlichia sp., A. bove., or T. luwenshuni. Our results revealed that a variety of tick-borne pathogens highly carried by these ticks, specially Ha longicornis. Therefore, it is necessary to make effective control of the ticks and the tick-borne diseases in the County.